PENGARUH SUHU TEMPERING TERHADAP SKD 11 MOD - Ariobimo, Rianti Dewi Sulamet (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
Tofulfill the demandofhigher toughnessand hardness, a chemical composition modification is madeto SKD-ll. and the modification result is known as SKD-l I Mod. Since the modification is done at thechemical composition then automatically it will change everything, including the heat treatment process andresult. This research, first ofall. is conducted in view ofthe modification factors, whilst, at the same time toexamine whether the producers specification can be achieved.